Ethical Politics, Teacher Ordinances, And Illegal Schools: A Genealogy Of Educational Discrimination In Indonesia - Fitri Mardiani; Syaharuddin Syaharuddin; Muhammad Rezky Noor Handy; Heri Susanto; Fathurrahman Fathurrahman (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
This study aims to unravel the roots of discrimination in Indonesian education through the implementation of ethical policies, teacher ordinances, and illegal schools during the Dutch colonial period. These discriminatory patterns were designed to maintain power. For example, the teacher ordinances (1905, 1925, 1932) and the illegal schools emphasized colonial state control through restrictions and even the elimination of educational rights. This article uses a library method, drawing on sources from books, websites, and relevant journals accessed using Google search engines, Google Scholar, the Open Access Library, and others. Ethical politics, a policy intended to improve the welfare of the colonial population, in fact, gave rise to educational segregation between indigenous and European groups. The patterns of segregation, ideological control, and unequal access to education during the colonial period have resonance today, namely through disparities in quality, access, and central policy control over learning spaces for communities in remote areas. Understanding the roots of this discrimination can serve as a basis for collective reflection to build a more just, inclusive, and relevant education system to meet the needs of the times.